1991
DOI: 10.1016/s0022-5347(17)38537-3
|View full text |Cite
|
Sign up to set email alerts
|

Urophonographic Studies of Benign Prostatic Hypertrophy

Abstract: The sonic detection and recording systems of urethral sounds generated during micturition were developed. This procedure was tentatively postulated as "urophonography" and its recording diagram as a "urophonogram". Classification of urophonograms was done on the basis of analyzing normal healthy male volunteers and patients with benign prostatic hyperplasia. Four types of urophonograms were demonstrated according to the shape and characteristics. Types 1, 2, 3 and 4 were characterized by a diamond shape, irreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…The sound recordings in this study are similar to the examples presented by Koiso et al 10 and Teriö. 16 The values for the weighted average frequency given by Teriö for the one volunteer in his study (112 and 129 Hz) are comparable to the values we found in our volunteer population (ranging from 125 to 240 Hz).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The sound recordings in this study are similar to the examples presented by Koiso et al 10 and Teriö. 16 The values for the weighted average frequency given by Teriö for the one volunteer in his study (112 and 129 Hz) are comparable to the values we found in our volunteer population (ranging from 125 to 240 Hz).…”
Section: Discussionsupporting
confidence: 84%
“…The development of this technique started in the mid-1960s with a voiding audiograph 9 and it has been applied in two clinical urophonographic studies. 10,11 The general conclusion from these two studies was that pressure variations at the urethral wall could be measured in the form of audible sound, both in a model as well as in patients. However, optimization of the transducer and recording equipment was needed for urophonographic assessment of urethral obstruction in patients.…”
Section: Introductionmentioning
confidence: 99%
“…The mean power frequency [Teri˛, 1991] (equivalent of the essential frequency with di¡erent cut-o¡ frequencies) varied between 150 and 450 Hz and average power was found between 300 and 750 Hz [van Koeveringe and van Mastrigt, 1991]. In males with BPH and in males after prostatectomy, power was found between 500 and 650 Hz [Koiso et al, 1991]. In our present study we calculated essential frequencies between 150 and 400 Hz in PVA-urethras.…”
Section: Discussionmentioning
confidence: 86%
“…Another decade later, experimental [Koiso et al, 1991;Teri˛, 1991] and clinical studies [Koiso et al, 1991;van Koeveringe and van Mastrigt, 1991] were published on the relation between noise recordings and bladder outlet obstruction. In the same period of time, studies were done on vascular murmurs caused by stenoses, a method referred to as phonoangiography [Lees and Forbes Dewey, 1970;Duncan et al, 1975;Tobin and Chang, 1976;Fredberg, 1977;Pitts and Forbes Dewey, 1979;Jones and Fronek, 1987].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation